Cyanobacterias and eukaryotes as part of the microbial community structure of biofilms in Copahue geothermal springs (Neuquén, Argentina) - Urbieta, María Sofía (2013)
Copahue is a geothermal field located in the Northwest corner of Neuquén province in Argentina. It is dominated by the still active Copahue volcano. In the area there are many acidic pools, hot springs and solfataras with different temperature and pH conditions that influence their microbial diversity. On the surrounding rocks and the borders of the pools, where water movements and thermal activity are less intense, many biofilms can be found. They have different aspects and structure, and they present less extreme temperature and pH conditions than the ponds and hot springs. Biofilms are a different ecological niche and they have different microbial community structure. In this study carried out by molecular ecology techniques, mainly 16S and 18S rRNA gene sequencing, we report a strong presence of cyanobacterias, cloroflexi and eukaryotes, not detected in previous biodiversity studies done on water samples. Almost no acidophilic bacteria were found, with the exception of members of genus Thiomonas, also found in the acidic pools. Archaea were detected only in one of the biofilms and the structure of that community seems to be similar to those found in water samples, with many uncultured species mainly related to order Sulfolobales. The aim of this study was to assess microbial community diversity in the biofilms present in this acidic geothermal area, with particular emphasis on detection of cyanobacteria and eukaryotes with potential biotechnological applications like production of alternative energy sources, synthesis and accumulation of biomolecules with antiviral or antibiotic activities or potential ability to bioremediate contaminated areas.